2014
DOI: 10.1073/pnas.1319316111
|View full text |Cite
|
Sign up to set email alerts
|

Mountain runoff vulnerability to increased evapotranspiration with vegetation expansion

Abstract: Climate change has the potential to reduce surface-water supply by expanding the activity, density, or coverage of upland vegetation, although the likelihood and severity of this effect are poorly known. We quantified the extent to which vegetation and evapotranspiration (ET) are presently cold-limited in California's upper Kings River basin and used a space-for-time substitution to calculate the sensitivity of riverflow to vegetation expansion. We found that runoff is highly sensitive to vegetation migration;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
172
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(188 citation statements)
references
References 32 publications
14
172
1
1
Order By: Relevance
“…On the other hand, an increase in the area of barren land that is free of snow cover for an extended time period could lead to an increase in recharge, offsetting to some degree the loss of recharge due to the increase in forest ET. This study's finding that elevations above 2000 m are disproportionally important to groundwater recharge is consistent with observations in the Southern Sierra Critical Zone Observatory [10,42]. NDVI derived estimates of annual evapotranspiration are below annual PRISM precipitation suggesting evapotranspiration is not water limited (Figure 11a).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, an increase in the area of barren land that is free of snow cover for an extended time period could lead to an increase in recharge, offsetting to some degree the loss of recharge due to the increase in forest ET. This study's finding that elevations above 2000 m are disproportionally important to groundwater recharge is consistent with observations in the Southern Sierra Critical Zone Observatory [10,42]. NDVI derived estimates of annual evapotranspiration are below annual PRISM precipitation suggesting evapotranspiration is not water limited (Figure 11a).…”
Section: Discussionsupporting
confidence: 87%
“…CIMIS, which uses weather data to determine average daily Eto for short grass, shows ET for this section of Mount Shasta ranging from 2.35 to 3.39 mm/day, or 858 to 1237 mm/year. As an alternative more appropriate for a mountainous region with conifer forests, we use the relationship described in Goulden and Bales (2014) [10] for watersheds across the Sierra Nevada, which they applied to estimate ET from normal difference vegetation index (NDVI) data (measured by the Moderate Resolution Imaging Spectroradiometer (MODIS) Aqua satellite and averaged for snow-and cloud-free periods). ET is calculated using the following regression between annual average NDVI and annual ET [10]:…”
Section: Spatial Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the first year of the drought occurring in 2012, Providence showed an increase in mean NDVI. This result could have been from greater potential ET from higher energy availability, as suggested with climate warming by Goulden and Bales [5], or from carryover water storage from the wettest year of 2011, as suggested by Safeeq and Hunsaker [19], or a combination of both. Garcia and Tague [54] also showed a high sensitivity of Sierra Nevada annual ET to plant available water capacity in subsurface storage, which would then influence the NDVI value.…”
Section: Vegetation Indicesmentioning
confidence: 99%
“…Results from Landsat image studies have shown that canopy green leaf cover typically increases rapidly over the first five years following a standreplacing disturbance, doubling in value by about 10 years after the disturbance, and then leveling off to approach pre-disturbance (mature) stand values by about 25 -30 years after the disturbance event (Potter, 2014a). In addition, annual vegetation evapotranspiration (ET) flux in montane and sub-alpine communities of the western U. S. has been closely correlated with satellite NDVI (Goulden & Bales, 2014).…”
mentioning
confidence: 99%